FIELD APPROACH IN THE PARTS OF SPEECH INTERACTION - Elena V. Murugova (Advanced Engineering Research, 2011)
The problems of parts of speech interaction with the application of field theory revealing the systematic ties within the vocabulary system, the existence of synchronic and diachronic, implicit and explicit, syntagmatic and paradigmatic, direct and indirect, motivated and idiomatic relationships between language items, dependence of word-building meaning of any derived word on a structural, semantic character of its word-building bases giving a wide-ranging analysis of parts of speech interaction in the linguacreative activity of people are considered.